2018
DOI: 10.1111/jvim.15236
|View full text |Cite
|
Sign up to set email alerts
|

Newborn foal with atypical myopathy

Abstract: The case of atypical myopathy (AM) in newborn Haflinger foal with clinical signs of depression and weakness appearing 6 hours after birth resulting in recumbency 12 hours after birth is described. The foal's dam was diagnosed with AM in the 6th month of gestation based on clinical signs of a myopathy, elevated serum activity of creatine kinase, metabolomic analysis and the presence of methylenecyclopropyl acetyl carnitine (MCPA‐carnitine) in the blood. At the time of delivery, the mare was grazing on a pasture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…However, direct ingestion of seedlings by lambs cannot be ruled out, though we believe it is unlikely as these animals were under 2 weeks of age. Potential milk excretion of HGA and/or its metabolite as the cause of AM in a neonatal foal has been suggested 53 . Because of the increasing evidence of this excretion route, toxicity of HGA via ingestion of ruminant milk should be considered a possible risk for human health and warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…However, direct ingestion of seedlings by lambs cannot be ruled out, though we believe it is unlikely as these animals were under 2 weeks of age. Potential milk excretion of HGA and/or its metabolite as the cause of AM in a neonatal foal has been suggested 53 . Because of the increasing evidence of this excretion route, toxicity of HGA via ingestion of ruminant milk should be considered a possible risk for human health and warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…HGA and MCPrG were detected in some rumen and faeces extracts, and MCPrG was also detected in the liver of the affected milus. Two links to the food chain should be briefly addressed here: (a) there is a question of whether the consumption of offal, such as the liver or kidneys, but also meat and other products from affected wild or domestic ruminants by humans is safe, and this remains unclear at the moment; (b) a possible transfer of HGA into milk or at least a diaplacentar transfer was shown in a lactating mare affected by AM, and subsequent intake by the foal led to intoxication and sudden death within a few hours after birth (Karlíková et al., 2018). Therefore, intoxication may also occur, or at least cannot be excluded, from products of lactating animals used for human consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Literature mentions several cases of AM among gravid mares and in unweaned foals [ 2 ]. In 2018, Karlíková et al reported a newborn foal with signs of AM [ 16 ]. This case-report describes a foal born at full term from a mare which recovered from AM during the sixth month of pregnancy.…”
Section: Introductionmentioning
confidence: 99%